Recent Advances in Cyanine-Based Phototherapy Agents - Bilici, Kubra; Cetin, Sultan; Celikbas, Eda; Yagci Acar, Havva; Kolemen, Safacan (Frontiers in Chemistry, 2021)
Phototherapies, in the form of photodynamic therapy (PDT) and photothermal therapy (PTT), are very promising treatment modalities for cancer since they provide locality and turn-on mechanism for toxicity, both of which is critical in reducing off-site toxicity. Irradiation of photo-sensitive agents demonstrated successful therapeutic outcomes; however, each approach has its limitations and needs to be improved for clinic success. The combination of PTT and PDT may work in a synergistic way to overcome the limitations of each method and indeed improve the treatment efficacy. The development of single photo-sensitive agents capable of inducing both PDT and PTT is, therefore, is extremely advantageous and highly desired. Cyanine dyes are shown to have such potential, hence have been very popular in recent years. Luminescence of cyanine dyes renders them as phototheranostic molecules, reporting the localization of the photo-sensitive agent prior to irradiation to induce phototoxicity, hence allow image guided-phototherapy. In this review, we mainly focus on the cyanine dye-based phototherapy of different cancer cells, concentrating on the advancements achieved in the last ten years.